2020
DOI: 10.15835/nbha48412160
|View full text |Cite
|
Sign up to set email alerts
|

The cup plant (Silphium perfoliatum L.) – a viable solution for bioremediating soils polluted with heavy metals

Abstract: Heavy metal pollution, manifested by the accumulation, toxicity and persistence in soil, water, air, and living organisms, is a major environmental problem that requires energetic resolution. Mining tailing areas contain metal minerals such as Cu, Zn, Pb, Cr and Cd in high concentrations that pollute the environment and pose threats to human health. Phytoremediation represents a sustainable, long-term, and relatively inexpensive strategy, thus proving to be convenient for stabilizing and improving the environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…There are a limited number of studies in the literature on the tolerance of the species S. perfoliatum to stress caused by excess heavy metals. Our previous studies [14] that determined the BAF of S. Perfoliatum on heavy metal-polluted soils revealed values ranging from 1.04 in the petioles to 5.17 in the roots; in the same context, the bioaccumulation variation of Zn was between 1.01 in the petioles and 2.53 in the lamina. Additionally, values of the ability to concentrate in plants between 119 and 1056 mg kg −1 have been determined for Zn, which are directly dependent on the amount of metal existing in the soil [61].…”
Section: Bioaccumulation Factor Translocation Factor and Removal Effi...mentioning
confidence: 85%
See 3 more Smart Citations
“…There are a limited number of studies in the literature on the tolerance of the species S. perfoliatum to stress caused by excess heavy metals. Our previous studies [14] that determined the BAF of S. Perfoliatum on heavy metal-polluted soils revealed values ranging from 1.04 in the petioles to 5.17 in the roots; in the same context, the bioaccumulation variation of Zn was between 1.01 in the petioles and 2.53 in the lamina. Additionally, values of the ability to concentrate in plants between 119 and 1056 mg kg −1 have been determined for Zn, which are directly dependent on the amount of metal existing in the soil [61].…”
Section: Bioaccumulation Factor Translocation Factor and Removal Effi...mentioning
confidence: 85%
“…2.1. Biological Material-Silphium perfoliatum L. Plants Silphium perfoliatum belongs to the Asteraceae family, a species native to the North American prairies [59], which is used for decorative purposes [60], is cultivated as a fodder plant [61], and is used for the production of biofuels [62][63][64][65], but also for the phytoremediation of heavy metals in Ps [14,[66][67][68][69]. The growth rate is intense due to the deep root system, the aerial part formed by stems up to 3 m high [70], with large leaves of 85-120 cm 2 , which are numerous and oppositely arranged on the stems [71].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomass can be used to produce high calorific synthetic gas, a promising advanced fuel that can be produced by thermochemical gasification [21]. According to Romanian researchers, the potential for bioremediation of vegetation leaves of plants of Silphium perfoliatum L. growing in heavy metal-contaminated soil is quite high [22]. Lithuanian researchers also studied cup plants and found that in many cases growth conditions and nitrogen fertilization were two decisive factors for all studied parameters: number of stems per plant, stem height, green and dry masses, and yield [23].…”
Section: Introductionmentioning
confidence: 99%